Are HIV Seroconversions Among Young Men Who Have Sex With Men Associated With Social Network Proximity to Recently or Long-Term HIV-Infected Individuals?. (1st February 2018) - Morgan, Ethan; Skaathun, Britt; Duvoisin, Rebeccah; Michaels, Stuart; Schneider, John A.
Abstract : Abstract: Debate remains as to the relative HIV transmission contributions from individuals who are recently HIV-infected and individuals who have long-term infections. In this study, we examine the relationship between new HIV seroconversions occurring among young black men who have sex with men and network proximity to recently or long-term HIV-infected individuals. A cohort of young black men who have sex with men (N = 618) was generated through respondent-driven sampling across 3 waves. A recent HIV infection was defined as either: (1) a confirmed seroconversion ⩽9 months before interview date or (2) a laboratory confirmed acute infection; long-term HIV-infected individuals were defined as a diagnosis date ≥9 months before interview date. Respondent-driven sampling-weighted logistic regression was used to examine network proximity of HIV transmission events to HIV-infected individuals in the network. Within the cohort, 343 (55.5%) participants were identified as HIV seronegative at baseline. Of these, 33 (9.6%) seroconverted during the study period. The odds of seroconversion increased significantly with each additional recent HIV-infected individual in one's network [adjusted odds ratio = 12.96; 95% confidence interval: 5.69 to 29.50], but were not significantly altered by the number of long-term infected individuals in one's network. In addition, for each member of one's network who used pre-exposure prophylaxis, the odds of seroconversion decreased significantly (adjusted odds ratio = 0.44; 95% confidence interval: 0.20 to 0.96). Early diagnosis and treatment is a critical first step in the HIV care continuum and together with pre-exposure prophylaxis awareness and use are critical targets for disrupting the transmission of HIV through most at-risk networks.